Ranking the factors applied in simulation training leading to better traffic in Alexandria Port using AHP - Ashraf Mohamed Elsayed (Maritime Research and Technology, 2023)
There is risk of collisions in daily life, also these risks are doubled in the maritime industry ships. This study aims to identify the factors that lead to ships’ collisions by prioritizing them which are; vessel traffic, marine pilots, fairway traffic, navigation aids, and ship berthing. The data was collected from 30 experts and decision-makers in the maritime industry. The data was analyzed by the AHP Analytic Hierarchy Process (AHP) method to know the preferences. The results revealed that vessel traffic is the first item that causes ships’ crashes, then marine pilots, fairway traffic, navigation aids, ship berthing respectively. Keywords: ships’ collisions, vessel traffic, fairway traffic, navigation aids, ship berthing.   Received: 06 March 2023 Accepted:22 June 2023 Published: 17 July 2023